Hubungan antara Kadar Prokalsitonin Serum dan Skor SOFA sebagai Parameter Tingkat Keparahan Disfungsi Organ Pasien Sepsis yang Dirawat di ICU RSUP Dr. Sardjito - Setiandari, Kristina; Wisudarti, Calcarina Fitriani Retno; Rahardjo, Sri (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Background: Sepsis causes an increase in procalcitonin level by increased secretion of proinflammatory ytokines, increased expression of CD 14 and CD 16, decrease of neutrophil phagocytic activity, suppression of blast transformation from T cells and neutrophil malfunctions. Procalcitonin secretion increase with increasing the severity of sepsis. The severity of sepsis is determined by the severity of organ dysfunction. The more severe the sepsis the more severe the organ dysfunction occurs and the higher the procalcitonin secretion.Objective: The purpose of this study was to determine if there is a relationship between procalcitonin levels and SOFA score as a severity parameter of organ dysfunction in septic patients treated in ICU Dr Sardjito Hospital.Methods: The study design was prospective observational cohort study. A total of 29 septic patients, age above 18 years old treated in ICU Dr Sardjito Hospital Yogyakarta were included in this study. Procalcitonin serum was measured and the SOFA score were calculated at the day of admission or at the day the diagnosis of sepsis was made (Day-0), within 24 hours (Day-1), at Day-3 and at day-5. Spearman correlation was used to analize the correlation between procalcitonin levels and SOFA score.Result: The overall mean of SOFA score was 10.3+3.9 while overall mean of procalcitonin level was 59.2+58.7 ng/ml. Significant positive correlation was found between overall procalcitonin level and SOFA score (r=0.663; p<0.05). The significant positive correlation was also found at Day-0 (r= 0.601; p<0.05), Day-1 (r=0.675; p<0.05), Day-3 (r=0.754; p<0.05) and Day-5 (r=0.718; p<0.05).Conclusion: There is a significant strong positive correlation between procalcitonin levels and SOFA score as a severity parameter of organ dysfunction in septic patients treated in ICU Dr Sardjito Hospital.